Becoming a Professional: Online Discussion Boards as a Tool for Developing Professionalism Among MPH Students. (September 2016) - Merzel, Cheryl; Goodman, Andrew
Cultivating professionalism among students is a key goal of the Master of Public Health (MPH) practicum. Achieving this goal, however, can be pedagogically challenging. We provide guidance on implementing and using an online student discussion board as a vehicle for promoting professional development, based on our experience overseeing the MPH internship (practicum) at a large urban university school of public health. Our approach is derived from the professional development literature identifying active reflection on practice experiences as a critical means of facilitating the process of developing mastery and proficiency. We have found that an online discussion board provides a supportive environment for discussing numerous professional challenges encountered in the internship and sharing strategies for addressing these challenges. Our experience suggests that online discussion boards are a useful tool to help MPH students develop their professional skillset, conduct, and values.